The Potential Hepatoprotective Effect of Paeoniae Radix Alba in Thioacetamide-Induced Acute Liver Injury in Rats. (28th January 2022) - Shin, Mi-Rae; Lee, Se Hui; Roh, Seong-Soo
Abstract : Aim . Acute liver injury (ALI) can occur for various reasons by induced inflammation and apoptosis of liver cells including hepatocytes, Kupffer cells, and hepatic stellate cells. Thioacetamide (TAA), which is a classic hepatotoxin, causes oxidative stress, membrane damage, and accumulation of lipid droplets and subsequently provokes consecutive liver injury. In the current study, we tested whether Paeoniae Radix Alba (PR) could alleviate TAA-induced ALI. Methods . Thirty-five male rats were equally separated into five groups. The first group was the normal group, which received distilled water only. The remaining four groups received intraperitoneal TAA (200 mg/kg) for 3 days to induce ALI. The four groups were divided into the control group (no treatment), silymarin-treated, 100 mg/kg PR-treated, and 200 mg/kg PR-treated. The efficacy of PR against hepatotoxicity was evaluated in terms of the serum biochemical index and protein expression associated with inflammation and apoptosis. Moreover, the dissected livers were analyzed by hematoxylin and eosin stain. Results . PR alleviated liver dysfunction as evidenced by decreased levels of aspartate aminotransferase, alanine aminotransferase, and ammonia. Phosphorylated AMP-activated protein kinase (AMPK) and Sirtuin 1 (Sirt1) levels were obviously decreased in the TAA control group, whereas PR reversed these changes. PR also prevented deteriorative effects through inhibition of inflammation and apoptosis via nuclear transcription factor-kappa Bp65 (NF- κ Bp65) inactivation. Moreover, we found that the hepatoprotective effect of PR pretreatment was mediated by restoration of histopathological changes. Conclusion . PR efficiently blocked both the inflammatory response and apoptosis through activating the AMPK/Sirt1/NF- κ Bp65 pathway. Therefore, PR is considered a potential therapeutic agent against ALI.